Developing guidelines for the protection of older people in humanitarian emergencies - V Vijayakumar (Forced Migration Review, 2002)
The international community’s recent commitment toaddressing the issues facing older people, reflectedin the designation of 1999 as the International Yearof Older Persons, has begun to influence the workof humanitarian agencies.